2011
DOI: 10.4103/0019-5359.106612
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and relationship of human papilloma virus type 16 and type 18 with oral squamous cell carcinoma and oral leukoplakia in fresh scrappings: A PCR study

Abstract: HPV type 16, 18, and co-infection of both types showed high prevalence in oral squamous cell carcinoma.The prevalence of HPV type 18 was found to be higher than HPV type 16 and co-infection in oral leukoplakia. It was observed that the tongue and palate lesions in the oral squamous cell carcinoma patients showed high prevalence of HPV type 16, type 18, and co-infection compared with other sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Various studies analysed the impact of HPV infection on head and neck cancer with HPV positivity in 24%–73% of the investigated tumours (Jalouli et al., ; Mathew et al., ; Ostwald et al., ; Prakash et al., ). Although the role of HPV infections in the pathogenesis of oropharyngeal cancers is proven, the impact of oral HPV infection on development of OSCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies analysed the impact of HPV infection on head and neck cancer with HPV positivity in 24%–73% of the investigated tumours (Jalouli et al., ; Mathew et al., ; Ostwald et al., ; Prakash et al., ). Although the role of HPV infections in the pathogenesis of oropharyngeal cancers is proven, the impact of oral HPV infection on development of OSCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies analysed the impact of HPV infection on head and neck cancer with HPV positivity in 24%-73% of the investigated tumours (Jalouli et al, 2010;Mathew et al, 2011;Ostwald et al, 2003;Prakash et al, 2013). Although the role of HPV infections in could be shown, which was previously described mainly for OPSCC (Fakhry et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…HPV18 is the second most common HPV type found in cervical cancers [2, 18] and several studies have reported that HPV18 may have an equal or greater prevalence than HPV16 in HPV-associated oral cancer cases in countries including Brazil [20], the United Arab Emirates [21], Iran [22], and Taiwan [23]. We have previously generated two prototype therapeutic HPV DNA vaccines targeting HPV16-E6, the pcDNA3-HPV16-E6 (encoding wild type HPV16-E6 protein) and the pcDNA3-CRT/HPV16-E6 (encoding a fusion protein of HPV16-E6 with calreticulin) and evaluated the immunogenicity and antitumor effects of these vaccines in C57BL/6 mice [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the frequency of HPV-16 infection in OSCC ranges from 10.6 to 81.3 % using PCR 3,[23][24][25][26][27][28] . In this study, HPV-16 positivity rates among all PT specimens were 39.2 % (51/130), which is within the range reported in the above-mentioned study.…”
Section: Discussionmentioning
confidence: 99%